Influence of Learning Commitment and Parental Involvement on Self-regulated Learning of Senior High School Students - Calumno, Freddie John; Maria Rebecca R. Marfil (Jurnal Pendidikan, 2024)
This study investigated the influence of learning commitment and parental involvement on the self-regulated learning of senior high school students of Biñan Integrated National High School, SY 2021-2022. A descriptive correlational research design sought to establish findings to be used as a foundation for a self-regulated learning model that can be adopted in the advent of face-to-face learning in the new normal. The findings indicated that the students indicated a strong learning commitment, a high level of parental involvement, and a high level of self-regulated learning. As significant relationships between variables were regressed, the resulting model revealed that learning commitment, as an individual predictor, has the most substantial positive influence on all dimensions of self-regulated learning. The combined effect of parental involvement negated the influence of learning commitment on dimensions of self-regulated learning in terms of environment structuring, task strategies and help-seeking strategies. Coordinating time and vitality through self-regulated learning will result in a more compelling and fulfilling encounter, which may boost self-efficacy and inspiration. The study provides an adoptable model to optimize self-regulated learning, which is a skill set that may be taught and may be able to assist students in setting specific goals for themselves and evaluating their progress. Students who can self-regulate are more proactive and less reactive in their learning.